Investing in Human Capital and Its Role in Achieving Economic Development in Iraq - Mayada Rashid Kamel, (Technium Business and Management, 2024)
This research aims to identify the importance of activating the role of Human Capital (HC) in Iraq's education and health sectors, as well as to analyze the reality of investment in HC in the Iraqi economy and identify the challenges and appropriate policies to activate this investment. The research relied on the descriptive and analytical approach to HC and used data from 2011 - 2021. The research reached a set of conclusions, the most important of which is that HC has a vital role in the education and health sectors. In addition, Iraq suffers from several problems and challenges. In the crucial sectors for investing in HC, namely education, and health, there are also a group of adverse effects represented by high rates of poverty and unemployment among HC, in addition to the low level of health and the increasing numbers of dropouts from education.